Lone Wolf Terrorism in America: Using Knowledge of Radicalization Pathways to Forge Prevention Strategies, 1940-2013 - Hamm, Mark ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. Typically, NACJD's Fast Track Release requires all direct identifiers to be removed or masked. As the sources of information for this collection are publicly available, direct identifiers were left within the collection. This study created the largest and most comprehensive database ever created to date on lone wolf terrorism. It includes 1 Excel data file (LONEWOLF_NIJ_HAMM_SPAAIJ_2014_unlocked.xlsx; n=98, 23 variables). The information was gathered from an extensive review of previous research, biographies and memoirs, journalistic sources, government reports, court documents, encyclopedias and documentary films. Qualitative interviews were conducted as part of this research, but these interviews were not made available for archiving.